Ancestral Heritage in Traditional Medicine Among Coastal Communities in Indonesia: Spiritual Practices and Modern Integration - Ahsan, Zikri Raudhatul; Samnuzulsari, Tri; Niko, Nikodemus (Yayasan Ilomata, 2025)
This study examines the ancestral heritage in traditional medicine practices among coastal communities in Indonesia through a literature review approach. Rooted in local knowledge and spiritual beliefs passed down through generations, these practices involve the use of natural resources, particularly medicinal plants, alongside rituals and prayers that balance the spiritual and physical realms. Using a literature review method, this study identifies, analyzes, and synthesizes relevant research to gain a deeper understanding of traditional medicine, with data sourced from leading academic databases such as Scopus, focusing on English-language publications from 1988 to 2024. The findings reveal that traditional medicine extends beyond physical healing, emphasizing harmony between humans, nature, and spiritual forces. Despite the influence of modern medical practices, traditional healing remains integral to healthcare, offering alternative approaches to various health concerns. The study underscores the importance of preserving traditional knowledge through systematic documentation and scientific inquiry while highlighting the potential for integrating traditional and modern medicine to develop a more holistic healthcare approach. By deepening the understanding of the cultural and health values inherent in traditional healing, this study promotes its sustainability amid globalization.